Estudio de la variación hereditaria de líneas F2 de arroz (Oryza sativa L. ssp. indica) resultantes de cruzamientos con un progenitor masculino portador del gen CREALFIELD - Panches Ayala, Genesis Nathali (2020)
This experimental trial was carried out using plantlets rice F2 lines (Oryza sativa L. ssp. indica) resulting from crossings with a male parent, carrier of the CREALFIELD gene, which confers resistance to the herbicide imazetapir. This research was conducted at the “San Pablo” farm, belonging to the Faculty of Agricultural Sciences, Technical University of Babahoyo, located at Km 7.5 of the Babahoyo –Montalvo road. The objectives were the following: 1). To determine the effect of the herbicide imazetapir on rice F2 plantlets, segregating from a male parent carrying the CLEARFIELD gene. 2). To establish the hereditary variability of the segregating populations under study and; 3). To select F2 segregating rice tolerant and / or resistant to imazetapir herbicide. The variables evaluated were the following: Chlorophyll content, Number of dead plants, Number of living plants, Number of total plants and Degree of toxicity of the herbicide Imazetapir (ALAM scale). The Br-101-UTB genotype, which is the parent with Imazetapir resistance, was lowest affected; however, it should be noted that in these results, there were two progenies that were severely affected, such as the FI-107 / BR-101-UTB and FL-109 / BR-101-UTB with more than 90% damage, resulting in the death of individuals. These results indicate that when the BR-101-UTB cultivar is used as a male parent, the imazetapir herbicide resistance gene may not be transferred to the progeny and will depend on the female parent used. The nine progenies that survived the application of the herbicide imazetapir, were in the low range of 7.71 to 22.73%. The parents were severely affected, including Puyón, except for the parent BR-101-UTB, which is the parent that contains the herbicide resistance gene.